Analisis Mobilitas Ulang Alik Pekerja - Yasmin Putri Derin Tsa; Atih Rohaeti Dariah (Bandung Conference Series: Economics Studies, 2022)
Abstract. The large number of economic activities in Sukajadi Subdistrict does not prevent Sukawarna Village from the phenomenon of unemployment because the existing job opportunities are not only owned for local residents but also for residents outside the Sukajadi District area. This study aims to determine: (1) the characteristics of non-resident workers in Sukawarna Sub-district working in Sukajadi District and (2) factors causing non-resident workers in Sukawarna Sub-district to work in Sukajadi District. The data used in this study are primary and secondary data sourced from interviews using a list of questions that have been prepared for workers who do shuttle in Sukajadi District. The research method used is descriptive qualitative method. Based on the results of the study, the characteristics of workers are characterized by high school / vocational education backgrounds with a productive age range of 25-35 years, dominated by women with the most regional origins from Cimahi District. The factors that cause non-resident workers from Sukawarna Sub-district to work in Sukajadi District are due to job opportunities that match their qualifications and abilities and get better income due to insufficient needs compared to working in their home area. Abstrak. Banyaknya aktivitas ekonomi di Kecamatan Sukajadi tidak menjadikan Kelurahan Sukawarna terhindar dari fenomena pengangguran karena kesempatan kerja yang ada tidak hanya dimiliki untuk penduduk setempat namun juga untuk penduduk diluar wilayah Kecamatan Sukajadi. Penelitian ini bertujuan untuk mengetahui: (1) karakteristik pekerja bukan penduduk Kelurahan Sukawarna bekerja di Kecamatan Sukajadi dan (2) faktor penyebab pekerja bukan penduduk Kelurahan Sukawarna bekerja di Kecamatan Sukajadi. Data yang digunakan dalam penelitian ini adalah data primer dan sekunder yang bersumber dari wawancara dengan menggunakan daftar pertanyaan yang telah dipersiapkan untuk tenaga kerja yang melakukan ulang alik di Kecamatan Sukajadi. Metode penelitian yang digunakan adalah metode kualitatif deskriptif. Berdasarkan hasil penelitian bahwa karakteristik pekerja bercirikan latar belakang pendidikan SMA/SMK dengan rentang usia produktif 25-35 tahun, di dominasi oleh perempuan dengan asal daerah terbanyak dari Kecamatan Cimahi. Faktor penyebab pekerja bukan penduduk Kelurahan Sukawarna bekerja di Kecamatan Sukajadi karena kesempatan kerja yang sesuai dengan kualifikasi kemampuan yang dimiliki serta mendapatkan penghasilan yang lebih baik karena kebutuhan yang tidak mencukupi dibanding bekerja di daerah asalnya.